Renal Biopsy in 100 cases of significant Proteinuria - Khan, Yaseen; Noor, Muhammad; Ghaffar, Rehmat (Journal of Postgraduate Medical Institute, 2011)
Proteinuria is a common manifestation of Glomerular disease which may or may not be accompanied by haematuria and renal impairement. We conducted a prospective study to asses the value of renal biopsy, complications and the type of renal pathology at the department of Medicine HMC, Peshawar from Sepetember 1998 to 2001. One hundred (100) patients having significant proteinuria, confirmed on 24 hours urinary protein urinary estimation underwent ultrasound guided renal biopsy. Intially tru cut needles were used but later on monopty gun was used. There were 70 male patients (70%) and 30 female patients (30%); the mean age at present was 29.5 years (range 10 - 90 years). All patients tolerated the procedure well and there were no failure. The common complications noted were pain at biopsy site in 15 patients (15%), gross haematuria in 10 patients (10%). None of the patients needed blood transfusion or prolonged hospitalization. Nephrotic syndrome was the most common indication for biopsy followed by lupus nephritis and interstitial nephritis. Among the nephrotic patients, minimal change disease and post infectious glomerulonephritis (GN) were the commonest findings in patients below the age of 25 years, membrano - proliferative GN ranked first in adults while membranous GN and amyloidosis were more common in the elderly. We concluded that renal biopsy is associated with an acceptably low rate of complications in our practice and that the pattern of renal histology varies slightly from those reported from other countires.